2016
DOI: 10.1155/2016/9852194
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Methodologies Employed for Visual Evoked Potentials

Abstract: Visual information is fundamental to how we appreciate our environment and interact with others. The visual evoked potential (VEP) is among those evoked potentials that are the bioelectric signals generated in the striate and extrastriate cortex when the retina is stimulated with light which can be recorded from the scalp electrodes. In the current paper, we provide an overview of the various modalities, techniques, and methodologies which have been employed for visual evoked potentials over the years. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 26 publications
0
25
0
5
Order By: Relevance
“…The time windows of these two components are fairly congruent with previous "brain microstate" EEG studies on action processing, which identified periods of stability in the brain activity between roughly 0 and 120-ms over the visual cortex and between roughly 120 and 200-ms over the posterior temporal and inferior parietal cortices 16,17 . The P100 component is routinely used in ophthalmology to evaluate the integrity of the visual cortices 44,45 , and the N170 has been shown to be particularly sensitive to inversion effects (comparison between upright/upside-down pictures) of body parts and, to a lesser extent, of objects 42,46 . Both components have been linked to the activity of the visual cortices, the P100 being generated by the primary visual cortex, and the N170 by the associative visual cortices at the border of the temporal and parietal cortices 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The time windows of these two components are fairly congruent with previous "brain microstate" EEG studies on action processing, which identified periods of stability in the brain activity between roughly 0 and 120-ms over the visual cortex and between roughly 120 and 200-ms over the posterior temporal and inferior parietal cortices 16,17 . The P100 component is routinely used in ophthalmology to evaluate the integrity of the visual cortices 44,45 , and the N170 has been shown to be particularly sensitive to inversion effects (comparison between upright/upside-down pictures) of body parts and, to a lesser extent, of objects 42,46 . Both components have been linked to the activity of the visual cortices, the P100 being generated by the primary visual cortex, and the N170 by the associative visual cortices at the border of the temporal and parietal cortices 42 .…”
Section: Discussionmentioning
confidence: 99%
“…First, compared to behavioral acuity, with decisions made quickly, VEP needs a longer time due to the requirement of sufficient data [ 144 ]. Next, the higher cognitive cortex is involved in the behavioral test, but VEP is only cellular activity in the primary visual cortex [ 145 ]. Finally, compared to the stationary targets of behavioral acuity, VEP acuity utilizes dynamic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Dışlama ölçütleri ise kronik 80 Tablo 1. Zenon ve ışık yayan diyot lamba ile elde edilen elektroretinografi kayıtlarındaki "a" ve "b" dalgalarının gecikme süreleri (ms) ve genlikleri (µV) "a" gecikme süresi "b" gecikme süresi "a" genliği "b" genliği (12,13).…”
Section: Gereç Ve Yöntemler öRneklemunclassified